(untitled) (Revista de Ciências Agroveterinárias, 2017)
Girdling consists of elimination of a small part of the cortex around a pre-selected branch, this technique being successfully applied in fruit trees. The aim of this study was to assess the effect of girdling period and types on branches of olive cultivars on their vegetative development and fructification. The study was conducted at the Epamig Experimental Farm, located in the municipality of Maria da Fé, MG, Brazil. Activities began in March 2012, with use of 7-year-old plants of the Ascolano 315, Grappolo 541 and Maria da Fé cultivars. Three periods were assessed (March, April and May/12) and two types of girdling (10 and 15 mm), plus the control (without girdling). A randomized block experimental design was used with a split plot, three replications and one plant per plot. After girdling, the branches of the plants were assessed, with mean branch length (m), branch diameter near the girdle (mm), diameter of the branch base (mm) and fruit harvest (kg) as variables. It was concluded that the girdling technique did not affect the length and diameter of the branches of the three cultivars. Superior results were found in olive tree branches girdling in March and May. The fruits collected were positively affected by girdling of the branches.